Analisis Sistem Akuntansi Penerimaan Dan Pengeluaran Kas Pada PT. Riau Terkini Utama - sabania, Desti; Sari, Maya Rizki; Menhard, Menhard (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to analyze the cash receipts and disbursement accounting system at PT. Riau Terkini Utama with qualitative methods. PT. Riau Terkini is a company engaged in business, namely Web Portals/News sites, the form of a Limited Liability Company. The development of information and communication technology today is much faster than imagined by many parties. In Indonesia, almost 18 million Indonesians are internet literate and will continue to increase at any time. Indonesia is currently experiencing a very rapid development of digital media. Each company is required to apply an accounting system that is in accordance with the conditions of each company. One of the systems used by the company is the cash receipts and disbursement accounting system. Cash problems are matters that require special handling, especially in administration, both for large, medium and small companies. Because in principle cash is a current asset that has the most liquid nature and is easily transferable. As an Information Technology-based mass media, Riauterkini.com can be accessed anywhere, all over the world. This can be proven by the various countries of origin of Riauterkini.com visitors. Until now more than 50 countries have been the origin of visitors to Riauterkini.com. To overcome these problems an internal control system is needed to optimize existing resources and minimize unwanted things that will harm the company. Optimizing resources means increasing the accuracy and thoroughness of data and creating reliable accounting data in its records. While minimizing unwanted things aims to maintain and protect company assets, for example reducing errors, fraud and damage.